Evaluation of the Wondfo G6PD/Hb Test for glucose-6-phosphate dehydrogenase deficiency: preliminary performance, matrix equivalence, and usability - Rebecca K. Green; Stephanie Zobrist; Gornpan Gornsawun; Paw Khu Moo; Laypaw Archasuksan; Huyen Nguyen; Huong Nguyen; Cindy S. Chu; Emily Gerth-Guyette; Podjanee Jittamala; François Nosten; Sampa Pal; et al. (Malaria Journal)
Abstract Background Current treatment guidelines for radical cure of Plasmodium vivax malaria recommend the use of 8-aminoquinolines, which can result in life-threatening complications in people with glucose-6-phsophate dehydrogenase (G6PD) deficiency. Testing for this condition is recommended prior to administering such drugs. The Wondfo G6PD/Hb Test (Guangzhou Wondfo Biotech Co., Ltd., China) is a novel, quantitative point-of-care (POC) G6PD test that may help decentralize testing, expanding access to safe treatment options. Methods Two studies were conducted: a retrospective diagnostic accuracy study on frozen venous whole blood specimens and a prospective matrix equivalency study. First, 300 frozen specimens from Mae Sot, Thailand were tested from July–August 2022 using the Wondfo test in laboratory and simulated field conditions. Reference testing for G6PD and Hb (spectrophotometer [Pointe Scientific, USA] and HemoCue [HemoCue AB, Sweden], respectively) was completed in the laboratory. Usability was evaluated among 10 intended users. Next, 225 participants were enrolled into a prospective matrix equivalency study from March–May 2023 in Memphis, Tennessee, USA. The Wondfo test was conducted at the POC with fingerstick capillary blood, and Wondfo and HemoCue tests were completed on fresh venous (K2EDTA) blood within 12 h. Remaining specimens were shipped to PATH for repeat Wondfo and reference testing. Results The Wondfo G6PD measurement showed strong correlation under both laboratory and field conditions (R2>0.9). The area under the curve was 1.00 for deficient (95% CI: 1.00–1.00) and 0.99 for intermediate individuals (95% CI: 0.99–1.00). Sensitivity was high (1.00) across all conditions and groups (lower bound of the 95% CI ≥0.85). Good correlation was observed in both capillary and fresh venous blood against the reference and each other (R2>0.75). McNemar’s test showed no significant differences in classification between venous and capillary specimens. The Wondfo test achieved 98.2% (95%CI: 95.5–99.5%) overall agreement. All usability participants successfully completed quality control and test procedures, rating the test system highly for ease of use. Conclusions The Wondfo G6PD/Hb Test demonstrates good diagnostic performance using current manufacturer thresholds across various conditions and both venous and capillary specimens. Comparable performance in both specimen types supports matrix equivalence. Usability is acceptable for end users, though refinements were recommended.